Incidence and threat factors of anastomotic leak following emergency abdominal surgery: a retrospective analysis - Ghugare, Ravindra Shankar (International Surgery Journal, 2025)
Background: Anastomotic leakage (AL) represents a critical postoperative complication that is linked to considerable morbidity and mortality in the context of abdominal surgery. Methods: This retrospective (RTS) analysis assessed a cohort of 2,563 patients who underwent emergency abdominal surgery involving bowel resection and anastomosis at two tertiary centres in India over the period from 2015 to 2023. Results: The total occurrence of AL was recorded at 3.47%. Univariate analysis revealed multiple clinical and operative variables that are significantly correlated with AL. Analysis using multivariate logistic regression identified hypoalbuminemia, the perioperative transfusion of two or more units of blood, peritoneal contamination and male sex as independent threat factors. Patients diagnosed with AL exhibited an elevated incidence of reoperation, extended durations of hospitalization and a heightened rate of in-hospital mortality. Conclusions: Identifying these threat factors is essential for enhancing perioperative management and informing surgical decision-making in patients at high threat who are undergoing emergency abdominal procedures.